2017
DOI: 10.24953/turkjped.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Cow`s milk protein allergy awareness and practice among Turkish pediatricians: A questionnaire-survey

Abstract: Region-specific recommendations for the prevention, diagnosis, and treatment of cow's milk protein allergy (CMPA) are not available in Turkey. This crosssectional questionnaire-survey was designed to evaluate CMPA awareness and practice among Turkish pediatricians. A total of 410 pediatricians were included based on their voluntary participation. Questionnaires elicited demographic data and pediatricians' awareness and practice of CMPA in infants and children. Atopic dermatitis (91.5%), diarrhea (88.0%) and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…This study showed that, most of pediatricians were general pediatricians (78.1%). This agrees with Yüce et al (4) who made cross-sectional questionnairesurvey that was designed to evaluate CMPA awareness and practice among Turkish pediatricians. A total of 410 pediatricians were included based on their voluntary participation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This study showed that, most of pediatricians were general pediatricians (78.1%). This agrees with Yüce et al (4) who made cross-sectional questionnairesurvey that was designed to evaluate CMPA awareness and practice among Turkish pediatricians. A total of 410 pediatricians were included based on their voluntary participation.…”
Section: Discussionsupporting
confidence: 88%
“…Yüce et al (4) found accordingly, majority of their pediatricians considered atopic dermatitis, diarrhea, blood in stool and colic to be suggestive of CMPA. Overall, colonoscopy was the most common diagnostic test considered by pediatricians (85.5%) to be not the first priority in evaluation of a welldeveloped infant presenting with flecks or streaks of blood in stool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eliminasyon ile 72 saatte dışkıda kan kaybolur. Klinik olarak ilk birkaç yıl içinde besine tolerans gelişir (8,9).…”
Section: Discussionunclassified
“…10,11 Currently only few data exist that describe practices in the diagnosis and management of FA among pediatricians in Turkey. 12 Similar studies that evaluated the FA-related practices of primary care physicians (PCP) and/or pediatricians in the US, Finland, Kuwait, Australia and Croatia have consistently demonstrated significant deficits. [13][14][15][16][17] Given the developing need for the physicians to adapt themselves to recent changes in FA management, the wide range of different clinical presentations of IgE and non-IgE mediated FA, and the impacts of FA and diet restrictions on the patient's quality of life we prepared this survey to describe the FA knowledge and practices of general pediatricians, pediatric allergists and pediatric gastroenterologists.…”
mentioning
confidence: 99%